Drug Pricing Decisions and Insurance Coverage: Evidence from Medicare Part D - Benedic N. Ippolito; Joseph F. Levy (American Enterprise Institute (AEI), 2023)
We examine whether the pricing of brand drugs, relative to estimates of their clinical value, is related to the way insurers cover those products in Medicare Part D. The net prices of drugs in our sample vary significantly relative to value-based prices from the Institute for Clinical and Economic Review (ICER), indicating meaningfully different pricing strategies. Coverage decisions, formulary placement, and use of utilization management are clearly responsive to first-order differences in costs of products generally. However, among the subset of relatively high-cost products with value-based price estimates, we observe little relationship between pricing strategies and extensive margin coverage decisions. Plans that cover larger shares of lower-value products tend to have permissive coverage policies and higher resulting premiums. Among potential explanations, we highlight institutional features that may help explain these results and propose an empirical test surrounding upcoming policy changes due to the Inflation Reduction Act.
Keywords: 330